Kemasan Karton - Lilis Suryati (Balai Besar Kimia dan Kemasan, 1985)
Packaging Industry in Indonesia was started in 1969. The Packaging is very important in trade, because the packaging will be used in the promotion and the protection for product. The Packaging have the various type.There are corrugated and paper box packaging.